E-learning and social media motivation factor model - Saleh, Nor Shela; Rosli, Mohd Shafie; Aris, Baharuddin; Ahmad, Maizah Hura; Abjoli Sejzi, Abbas; Shamsudin, Nur Amalina (Canadian Center of Science and Education, 2015)
The aims of this study are to probe into the motivational factors toward the usage of e-learning and social media among educational technology postgraduate students in the Faculty of Education, Universiti Teknologi Malaysia. This study had involved 70 respondents via the means of a questionnaire. Four factors have been studied, named, the factor of technology, exposure, content and social influence. Via Structural Equation Modeling (SEM), this research uncovers that respondents usage of e-learning is being motivated by the factor of technology and content. The respondents use of social media was found to be motivated by the factor of technology and social influence. A strong positive relationship exists between the usage of e-learning and social media suggesting that social media can be manipulated as supporting material for e-learning. Yet, the finding may not be generalized to all Malaysian educational technology postgraduate students.